A SUCCESSFUL EXAMPLE OF DIAGNOSTICS AND TREATMENT OF AMBOLIUM WATER - Дарья Андреевна Масленкова; Светлана Федоровна Калинина; Екатерина Юрьевна Григорьева; Людмила Владимировна Ренге (The Publishing House Medicine and Enlightenment, 2020)
Amniotic fluid embolism is dangerous complication of pregnancy and childbirth, that is lethal in 80 percent of cases. The article presents a clinical case of successful treatment of amniotic fluid embolism (and related complications) in patient with predisposing factors for the development of disease. The clinical course, the laboratory changes, the details of manegment, and the course of the postpartum period are described in detail. Because of the lack of clear diagnostic criteria of amniotic fluid embolism and the polymorphism of the clinical picture of the disease, further investigation is still required.